Dissemination of some Antibiotic Resistance in Pseudomonas aeruginosa Isolates in Al-Diwaniya Hospitals. - Alramahy, Syoof Khowman; Falh Aladily, Zainab (Al-Qadisiyah Journal of Pure Science, 2018)
Pseudomonas aeruginosa is one of the primary opportunistic pathogens responsible for nosocomial infections. Aminoglycosides and quinolones are an important component of antipseudomonal chemotherapy. The inactivation of aminoglycosides by modifying enzymes and 16S rRNA methylase are the most common mechanisms of aminoglycoside resistance , As for The inactivation of quinolones by occurrence of mutation encoded in the genes for the production of DNA gyrase and Topoisomerase-IV enzymes .The goal of the present study was to investigate the occurrence of aminoglycoside and quinolones resistance and the incidence of important modifying enzyme and 16S rRNA methylase genes in P. aeruginosa isolates in Al-Diwaniya Teaching Hospital. The samples of the study were collected from various sources and they were 350 samples from ear, burn, sputum, and urinary tract infections were examined for the detection of P. aeruginosa in Al-Diwaniya Teaching Hospital for the period from November 2014 to March 2015, the results of cultural and biochemical tests showed that 50 isolate belong to P. aeruginosa and their diagnosis were confirmed by API-20E . The antibiotic resistance profiles of the all isolates were determined by disk diffusion method of Kirby-Bauer against six antipseudomonal agents belonging to two classes. A total of 50 (14.2%) isolates of P. aeruginosa were identified in the study period . Thirty-two (64%) isolates were found to be resistant to at least one aminoglycosides tested; with gentamicin being the highest (64%) and amikacin (26%) the lowest. Moderate resistance rates were exhibited against ciprofloxacin (20%) and norfloxacin (14%).